The evaluation of the relationship between firms information quality with loans accreditation Iranian bank - Hassan Ghodrati; Ramin Nouri (Management Science Letters, 2013)
This research aims to study the effects of the quality of financial information companies on the accreditation of loans and bank contracts of the branches of Bank Mellat in the East Azerbaijan province. This is an applied research using 67 branches of Bank Mellat of the East Azerbaijan province. The study chooses a sample of 31 branches to evaluate the effects of the quality of financial information companies on the accreditation of loans and bank contracts. There are variables associated with quality of financial information such as their relevance, timeliness, and reliability over the period 2010-2011 using multi-variables linear-regression technique. The results of this study show that relevance, timeliness, and reliability variables are effective on the accreditation of loans and bank contracts of the branches.